2022
DOI: 10.1093/mnras/stac675
|View full text |Cite
|
Sign up to set email alerts
|

The eccentricity distribution of wide binaries and their individual measurements

Abstract: Eccentricity of wide binaries is difficult to measure due to their long orbital periods. With Gaia’s high-precision astrometric measurements, eccentricity of a wide binary can be constrained by the angle between the separation vector and the relative velocity vector (the v-r angle). In this paper, by using the v-r angles of wide binaries in Gaia Early Data Release 3, we develop a Bayesian approach to measure the eccentricity distribution as a function of binary separations. Furthermore, we infer the eccentrici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(104 citation statements)
references
References 79 publications
6
98
0
Order By: Relevance
“…These results may go some way to understanding the observed nonthermal (including superthermal) eccentricity distributions of wide binaries in the solar neighborhood (Tokovinin 2020;Hwang et al 2022). However, before strong conclusions can be drawn, both time dependence and scattering from passing stars must be incorporated into the model.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…These results may go some way to understanding the observed nonthermal (including superthermal) eccentricity distributions of wide binaries in the solar neighborhood (Tokovinin 2020;Hwang et al 2022). However, before strong conclusions can be drawn, both time dependence and scattering from passing stars must be incorporated into the model.…”
Section: Discussionmentioning
confidence: 95%
“…Of course there are many subtleties to be addressed before one can claim this comparison between theory and observation to be precise. To name just one, Hwang et al (2022) inferred their eccentricity DFs assuming an isotropic DF of binary orientations, whereas we have shown that the "special direction" picked out by the Galactic plane actually creates a nonisotropic DF in which e and i are correlated (and where the special values of i are easily predicted). In principle one could measure the joint e-i distribution of wide binaries and use it to distinguish the impact of Galactic tides compared to other dynamical effects/ formation channels.…”
Section: Implications For Wide Binaries In the Galaxymentioning
confidence: 91%
See 2 more Smart Citations
“…Let's look now at the predicted evolution of the eccentricity, for an equal mass binary of 50M total mass and three values for the eccentricity: e 0 = 0.5, 0.25, 0.1 at f low . We choose the highest eccentricity to be e 0 = 0.5 because is close to the average eccentricity for wide binaries [171]. Fig.…”
Section: Eccentric Slownessmentioning
confidence: 99%